Cottonmouth snake bites reported to the ToxIC North American snakebite registry 2013–2017. (3rd March 2020) - Domanski, K.; Kleinschmidt, K. C.; Greene, S.; Ruha, A. M.; Bebarta, V. S.; Onisko, N.; Campleman, S.; Brent, J.; Wax, P.; ,
Abstract: Introduction: The majority of venomous snake exposures in the United States are due to snakes from the subfamily Crotalinae (pit vipers). There are three types of US pit vipers: rattlesnakes ( Crotalus and Sisturus spp.) copperheads ( Agkistrodon contortrix ), and cottonmouths ( Agkistrodon piscivorus ) also known as water moccasins. Cottonmouth bites are reported less frequently than other pit viper envenomations, and data on cottonmouth envenomation are limited. Our objective was to describe the epidemiology, clinical manifestations, and management of cottonmouth envenomations using prospective data reported to the Toxicology Investigators Consortium's (ToxIC) North American Snakebite Registry (NASBR) Methods: Cottonmouth envenomation cases reported to NASBR for the period from January 1, 2013, through December 31, 2017 were reviewed. Variables collected included patient demographics, bite location, clinical manifestations, and management. Results: Thirty-one cottonmouth envenomations were reported. Most bites occurred in children aged 7–12 (39%). Most bites involved the lower extremity (72%). Intentional interaction with the snake occurred in three cases (10%). Swelling was the most reported clinical effect and occurred in all patients. Gastrointestinal symptoms were reported in 19% of patients, and 19% developed coagulopathy. Antivenom treatment was used in 84% of patients. Nineteen patients (61%) required hospital stays of >24 hours. Discussion: Our study represents the first systematic prospective data collection on cottonmouth bites. Our data demonstrate that cottonmouth envenomations cause primarily local effects and, occasionally, systemic toxicity. Our study also demonstrates that antivenom is often indicated for these envenomations per published guidelines and recommendations. Conclusions: Cottonmouth envenomations are relatively infrequent. However, they can cause significant local and systemic toxicity. Most cottonmouth envenomations in this series were treated with antivenom and were hospitalized beyond 24 hours.